Integrating Digital Technology and Social Capital in Tourism Marketing Strategies - Nugrahini Susantinah Wisnujati; Hary Sastrywanto; Anindya Prastiwi Setyawati (PROCURATIO: Jurnal Manajemen & Bisnis, 2026)
Purpose – This study examines how digital technology integration and social capital influence tourism income in a community-based tourism context. While digital marketing has become an essential strategy in modern tourism development, its effectiveness often depends on the strength of social relationships and community participation. This research aims to analyze the combined role of digital technology, social capital, and communication collaboration in improving tourism income in Ketapanrame Tourism Village, Mojokerto Regency, Indonesia. Design/method/approach – This study employs a quantitative explanatory approach using a cross-sectional survey. Data were collected from tourism stakeholders in Ketapanrame Village through a structured questionnaire using a five-point Likert scale. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS to evaluate the relationships among digital technology, social capital, communication collaboration, and tourism income. Findings – The findings reveal that social capital has the strongest positive and significant effect on tourism income, indicating that trust, community participation, and strong social networks play a crucial role in generating economic benefits from tourism activities. Digital technology significantly strengthens social capital but shows a weak and negative direct effect on tourism income, suggesting that the current use of digital technology has not yet been fully optimized to produce direct economic returns. Communication collaboration significantly supports stakeholder interaction; however, its relationship with tourism income appears negative, indicating that existing coordination mechanisms may still be inefficient or overly bureaucratic. Implications – The results highlight the importance of strengthening community social networks alongside digital transformation initiatives in tourism villages. Policymakers and tourism managers should focus on improving digital literacy, fostering participatory governance, and developing integrated community-based digital marketing strategies to maximize tourism income and ensure sustainable tourism development. Novelty/Originality – This study proposes an integrated techno-social tourism framework by combining the Technology Acceptance Model (TAM) and Social Capital Theory to explain tourism income generation in a rural tourism village context, an area that remains relatively underexplored in empirical tourism research.